2009
DOI: 10.1177/0265407509106716
|View full text |Cite
|
Sign up to set email alerts
|

Draining or gaining? The social networks of public housing movers in Boston

Abstract: The social networks of low-income residents have been simultaneously described as supportive, strained, localized, and limited in providing access to necessary resources and information. Using a longitudinal qualitative approach, this study investigated the social networks of low-income women in one US high-poverty public housing project. Existing sociological frameworks for studying networks did not fully capture the women's social ties, particularly their “draining” ties. As the women were relocated as part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 32 publications
3
86
0
1
Order By: Relevance
“…A rapidly growing body of literature has suggested that local social dynamics, specifically social capital and social cohesion, are powerful contributors to mental health (Aneshensel and Sucoff, 1996;Carpiano, 2006;Caughy et al, 2003;Cornwell and Waite, 2009;Curley, 2009;Fitzpatrick et al, 2005;Fitzpatrick and LaGory, 2000;Gary et al, 2007;Gutman and Sameroff, 2004;Kawachi and Berkman, 2001;Kim, 2010;Omata, 2012;Pearlin, 1989;Phan et al, 2009;Schulz et al, 2006;Thoits, 1995;Usher, 2007;Xue et al, 2005). Conclusions regarding the benefits of social capital and social cohesion are mixed, however, which reflects the complexity of the social processes by which they shape mental health, as well as lack of scholarly consensus on how to define and operationalize them.…”
Section: Social Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…A rapidly growing body of literature has suggested that local social dynamics, specifically social capital and social cohesion, are powerful contributors to mental health (Aneshensel and Sucoff, 1996;Carpiano, 2006;Caughy et al, 2003;Cornwell and Waite, 2009;Curley, 2009;Fitzpatrick et al, 2005;Fitzpatrick and LaGory, 2000;Gary et al, 2007;Gutman and Sameroff, 2004;Kawachi and Berkman, 2001;Kim, 2010;Omata, 2012;Pearlin, 1989;Phan et al, 2009;Schulz et al, 2006;Thoits, 1995;Usher, 2007;Xue et al, 2005). Conclusions regarding the benefits of social capital and social cohesion are mixed, however, which reflects the complexity of the social processes by which they shape mental health, as well as lack of scholarly consensus on how to define and operationalize them.…”
Section: Social Dynamicsmentioning
confidence: 99%
“…According to the latter perspective, social capital takes the form of actual or potential resources that derive from social networks (Bourdieu, 1986;Carpiano, 2006). Social capital can benefit mental health by providing an economic and psychological safety net in an environment that lacks sufficient opportunities to meet basic necessities (Aneshensel and Sucoff, 1996;Carpiano, 2006;Caughy et al, 2003;Cornwell and Waite, 2009;Curley, 2009;Fitzpatrick et al, 2005;Fitzpatrick and LaGory, 2000;Gary et al, 2007;Kawachi and Berkman, 2001;Kim, 2010;Omata, 2012;Pearlin, 1989;Phan et al, 2009;Ross et al, 2000;Sampson et al, 1997;Thoits, 1995;Usher, 2007;Xue et al, 2005). In disadvantaged contexts, social capital may be vital for assistance with day-to-day tasks and vital needs (e.g., economic assistance, providing food, lending goods, child care, household repairs, transportation).…”
Section: Social Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, by disrupting established support networks, moving may actually be detrimental to economic success (Curley 2009 (Goetz 2011). These externalities when combined with the difficulty of movers to integrate into new networks mean that mobility policies may actually result in a net reduction of social capital.…”
Section: Moving Peoplementioning
confidence: 99%